K metodologii antisthenovských studií: Diogenovský kynismus jako způsob života - Kokeš, Michal (Filosoﬁcký časopis)
Lívia Flachbartová’s monograph introduces us to a non-theoretical approach to Cynic practice in the person of Diogenes of Sinope, a literary figure who acted radically with his negation of rational generalizations. Antisthenes in all likelihood created the literary figure of Socrates to present his own epistemic position through him, thereby enabling the emergence of the literary figure Diogenes of Sinope. Understanding Antisthenes’ epistemology is also important for understanding the formation of our current approach to knowledge. Its relationship to the rival Platonic theory allows us to take a look at a critical moment in the development of this understanding. In this manner it is possible to continue with research that is based on the hermeneutic method, which was proposed by Michel Foucault in the last century and is being continued today by, for example, Vladislav Suvák. According to the author of the monograph being reviewed here, the hermeneutic method of proof consisting in the knowledge of the subject allows us to better evaluate Antisthenes’ contribution to the field of knowledge, which according to the surviving texts he gave expression to. In this study, we focus primarily on the monograph of Lívia Flachbartová and her interpretation of cynicism as a way of life. We also focus on two surviving writings authored by Antisthenes: the speeches of Ajax and Odysseus. This allows us to analyze the specifics of Antisthenes’ literary invention, linguistic devices, and methods of proof, which also appear in other authors of Socratic dialogues and in the later Cynics. An attempt to abstract the method of proof can contribute not only to a further approximation of Antisthenes’ specific approach to knowledge, but also to an analysis of his work with language.